INTEGRASI KONSEP PEWARIS, AHLI WARIS, HARTA WARIS, DAN MAWĀNI’ AL-IRTS DALAM KERANGKA KEADILAN DISTRIBUSI WARISAN ISLAM - Khaiyyul Millati Waddin, Aufal Hadliq; Ashari, Beni (UAS PRESS, 2025)
This study discusses the concepts of heirs, heirs’ rights, inheritance assets, and mawāni’ al-irts within the framework of justice in Islamic inheritance distribution, using the maqāṣid al-syarī’ah approach. The distribution of inheritance in Islamic law, based on the verses of the Qur’an, is often confronted with social justice challenges, particularly in the context of the unequal distribution of inheritance between males and females. By using a maqāṣidī perspective, this research examines how the objectives of sharia, such as the protection of wealth (ḥifẓ al-māl) and offspring (ḥifẓ al-nasl), can provide a basis for reinterpreting inheritance law to create a more equitable distribution, especially in increasingly complex modern societies. This approach allows Islamic inheritance law to be more relevant and responsive to the social, economic, and gender roles in families, while still maintaining the fundamental principles of Islamic law. The research methodology used in this study is a normative-qualitative approach, with an in-depth analysis of texts and literature on both classical and contemporary sources, as well as the application of the maqāṣidī approach in understanding Islamic inheritance law. The aim of this study is to examine and offer solutions for reconstructing a fairer inheritance distribution and to understand the relevance and application of maqāṣidī principles in the context of Islamic inheritance law in contemporary society.